Opportunities Of Using Chatgpt In Academic Writing: Perceptions Of The Philippines And Indonesian Students - Herda, Rozanah Katrina; Travero, Arnel S.; Kafabih, Abdullah; Koeswoyo, Alfatih Widiyadi; Sari, Risma Novita; Hakiki, Farrij Imam; Wahidah, Nikmatul (Wahana Pendidikan, 2024)
The widespread utilization of Artificial Intelligence (AI) has caused debate in education about whether it is allowed in academic writing. ChatGPT facilitates academic writing in the EFL context by generating ideas and refining language. It provides research support by suggesting sources and enhances clarity and coherence in papers on complex topics. This study aims to uncover students’ perception of using ChatGPT as one of the most popular AI in the writing context. This quantitative research with a causal-comparative design analyzed the data involving two groups of students from Indonesia and the Philippines (N=334). The instrument used in this research was a closed-ended questionnaire. The research findings showed that students enjoyed the integration of ChatGPT in their academic writing because its contribution has raised their confidence, decreased stress, and raised writing quality which leads to satisfaction in their writing.